2000
DOI: 10.1590/s0100-879x2000000900011
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-5 and interleukin-10 are major cytokines in cerebrospinal fluid from patients with active neurocysticercosis

Abstract: Neurocysticercosis (NCC) is a common neurological disorder especially in developing countries, caused by infection of the brain with encysted larvae of the tapeworm Taenia solium. Seizures are a common finding associated with this disease. The objective of the present study was to evaluate the correlation between the levels of various cytokines present in the cerebrospinal fluid (CSF) of patients with NCC and the severity of the disease. The levels of the cytokines IL-1ß, TNF-a, IL-5, IL-10 and IFN-g were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…Embora na literatura não haja relatos anteriores sobre esse processo patológico, sabe-se que várias substâncias, geralmente de natureza protéica, podem sofrer transformação e se depositarem como beta-fibrilas, dentre elas as imunoglobulinas e as citocinas. Rodrigues Jr e cols 27 demonstraram elevados níveis de citocinas no líquor de pacientes com neurocisticercose. Assim, conclui-se que pelo menos parte das beta-fibrilas encontradas possa estar relacionada à elevação dos níveis de interleucinas.…”
Section: Resultsunclassified
“…Embora na literatura não haja relatos anteriores sobre esse processo patológico, sabe-se que várias substâncias, geralmente de natureza protéica, podem sofrer transformação e se depositarem como beta-fibrilas, dentre elas as imunoglobulinas e as citocinas. Rodrigues Jr e cols 27 demonstraram elevados níveis de citocinas no líquor de pacientes com neurocisticercose. Assim, conclui-se que pelo menos parte das beta-fibrilas encontradas possa estar relacionada à elevação dos níveis de interleucinas.…”
Section: Resultsunclassified
“…Severe NCC is accompanied with increased eosinophilic infiltration in CSF and production of mixed Th1/Th2 cytokines (IL-5, IL-6 and IL-10). Disease severity increases with the number of cysticerci as patients having multiple cysts show higher expression of IL-5 and IL-6 than patients having single cyst [15][16][17]. Increased expressions of IgG, IgM, IgE, IL-1β, IL-6 and TNF-α were observed in the patients having cysts in the subarachnoid spaces.…”
Section: Cns Immune Response and Cytokinesmentioning
confidence: 99%
“…These alterations also exist with different stage, number and location of the cysts. The expression of both anti-and pro-inflammatory cytokines at the chronic NCC at necropsy and in CSF may be responsible for the heterogeneity in disease outcome [15,17].…”
Section: Cns Immune Response and Cytokinesmentioning
confidence: 99%
“…23,24 It has also been reported that IL-5 and IL-10 predominated in the cerebrospinal fluid (CSF) of patients with active NCC. 25 Cysteine, aspartic, and metalloprotease activities have been characterized in excretory/secretory (E/S) antigens from T. solium metacestodes. 26,27 Live metacestodes may release such proteases for parasite nutrition, and they may also induce a humoral immune response in the host.…”
Section: Introductionmentioning
confidence: 99%